2012
DOI: 10.4322/rca.2012.031
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de híbridos de milho verde em função da adubação nitrogenada de cobertura

Abstract: RESUMO: O objetivo foi avaliar o desempenho agronômico de 22 híbridos experimentais de milho para a produção de milho verde, submetidos a duas doses de adubação nitrogenada de cobertura (0 e 144 kg ha-1 , ambientes 1 e 2, respectivamente) na Estação Experimental do Campus Universitário de Gurupi-TO. O delineamento experimental utilizado foi de blocos casualizados, com duas repetições. Foram avaliadas variáveis de interesses agronômico e comercial para a produção de milho verde, sendo realizadas análises de var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
3
1
0
2
Order By: Relevance
“…Carmo et al (2012), applying 150 kg ha -1 of nitrogen in a summer crop in Palmeiras, Goiás State, Brazil. In the winter/spring season, nitrogen doses did not increase yield (Figure 3), agreeing with Aguiar et al (2012), which applied nitrogen doses from 0 to 144 kg ha -1 to sweet corn grown in Gurupi, Tocantins State, Brazil.…”
Section: Resultssupporting
confidence: 61%
“…Carmo et al (2012), applying 150 kg ha -1 of nitrogen in a summer crop in Palmeiras, Goiás State, Brazil. In the winter/spring season, nitrogen doses did not increase yield (Figure 3), agreeing with Aguiar et al (2012), which applied nitrogen doses from 0 to 144 kg ha -1 to sweet corn grown in Gurupi, Tocantins State, Brazil.…”
Section: Resultssupporting
confidence: 61%
“…The ED found were similar to those reported by Aguiar et al (2012) for a CTS; they found a mean ED of 4.60 cm, considering 22 sweet corn genotypes. The higher EL was found in the NTS (Table 4), however, the ears reached diameter and length means consistent with the commercial ear classification in both tillage systems, i.e., ED higher than 3 cm and EL higher than 15 cm (AGUIAR et al, 2012).…”
Section: Resultssupporting
confidence: 88%
“…The ED found were similar to those reported by Aguiar et al (2012) for a CTS; they found a mean ED of 4.60 cm, considering 22 sweet corn genotypes. The higher EL was found in the NTS (Table 4), however, the ears reached diameter and length means consistent with the commercial ear classification in both tillage systems, i.e., ED higher than 3 cm and EL higher than 15 cm (AGUIAR et al, 2012). The higher ear growth in the NTS, shown by the EL (Table 4), may be correlated to the soil cover in this system, which favors soil water storage and availability (FIGUEIREDO;RAMOS;TOSTES, 2008).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Várias estratégias podem ser tomadas com o intuito de aumentar a eficiência no uso de N, tais como a redução das doses de adubos (Aguiar et al, 2012) para níveis que sejam produtivos e seguros; a utilização de leguminosas em rotação, que fornecem N e melhoram várias características do solo; a fixação biológica de N em gramíneas; a agricultura de precisão, e a seleção e/ou o desenvolvimento de cultivares com maior eficiência no uso de N (Carvalho et al, 2012).…”
Section: Introductionunclassified